Changes in the rotational alignment of the tibial component in total knee arthroplasty for varus osteoarthritis - Guomin Li; Li Sun; Senlei Li; Kezhou Chen; Yankun Li; Rui Luo; Bo Li (BMC Musculoskeletal Disorders)
Abstract Purposes Currently, there is no gold standard for determining the rotational alignment of the tibial component in varus knee deformities. This study aims to identify an appropriate method for determining the rotational alignment of the tibial component in total knee arthroplasty (TKA) for varus osteoarthritis. Methods This study explores the relationship between varus angles and various anatomical landmarks to identify the optimal landmark. A total of 174 patients with varus knee osteoarthritis (OA) were recruited between June 2019 and June 2022. Results Statistical analysis and scatter plots revealed a significant negative correlation between the varus angle and the ATCC in all patients with knee OA. A significant positive correlation was observed between the varus angle and the patellar tendon (including PCL-PT and PCL-MSL) when the varus angle was ≤ 10°. However, the correlation between these parameters changed when the varus angle exceeded 10°. Conclusions The study provides new insights into the rotational alignment of the tibial component in TKA for varus osteoarthritis, emphasizing the need for individualized alignment strategies based on anatomical landmarks and varus angle severity. Level of evidence Level III, correlation study.